1989
DOI: 10.3171/jns.1989.71.2.0208
|View full text |Cite
|
Sign up to set email alerts
|

Nonoperative treatment of spinal epidural infections

Abstract: Spinal epidural infections were diagnosed before the onset of neurological deficits in six patients and treated nonsurgically. The diagnosis was based on the clinical presentation and on the results of myelography and computerized tomography scanning. Positive cultures were obtained from blood in all six patients, from aspiration of a paraspinous infection in two, and from a skin abscess and a pulmonary empyema in one patient each. Staphylococcus aureus was the causative organism in five cases. All patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
1
2

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(36 citation statements)
references
References 10 publications
0
33
1
2
Order By: Relevance
“…Epidural abscesses have been treated successfully with intravenous antibiotics alone. However, these were in older adults with minor neurologic deficit [5,6]. In infants surgery is the preferred option; in one review, six of seven children who did not have an operation (because of missed diagnoses or they were considered too ill for general anaesthesia) died [8].…”
Section: Discussionmentioning
confidence: 99%
“…Epidural abscesses have been treated successfully with intravenous antibiotics alone. However, these were in older adults with minor neurologic deficit [5,6]. In infants surgery is the preferred option; in one review, six of seven children who did not have an operation (because of missed diagnoses or they were considered too ill for general anaesthesia) died [8].…”
Section: Discussionmentioning
confidence: 99%
“…Although 62% of blood cultures gives a positive result, 90% of abscesses material and 19% of the liquor can result in a specific germ (Angtuaco et al, 1987;Reihsaus et al, 2000;Sendi et al, 2008). The most common site of infection is the thoracolumbar region, due to the greater presence of fatty tissue, vascularization and lower adherence of the dura mater to the cord, as observed in this case (L4 to S1) (Grewal et al, 2006;Mampalam et al, 1989;Simpson et al, 1999).…”
Section: Discussionmentioning
confidence: 60%
“…If the paralysis persists for more than 36 to 48 h, nonsurgical approach is recommended (Mampalam et al, 1989). In cases without acute neurological involvement, diagnostic aspiration followed by antibiotic therapy for 4 to 8 weeks may be a reasonable choice (Angtuaco et al, 1987;Bremer and Darouiche, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have shown satisfactory results in patients treated non-operatively [10,11,17,18]. Leys et al [10] proposed four indications for the non-surgical m a n a g e m e n t of SEA.…”
Section: Discussionmentioning
confidence: 99%